Campur Kode Bahasa Arab dan Bahasa Indonesia dalam Percakapan Sehari-Hari Santri Putri Pondok Pesantren Dārul Lugah Waddirāsātil Islāmiyah Seninan Akkor Palengaan Pamekasan Madura - Satiyah (Jurusan Pendidikan Bahasa Arab, 2025)
Pesantren constitute an environment in which code-mixing is highly likely to occur, as they simultaneously teach two foreign languages. This study aims to describe the forms of code-mixing, the contributing factors, and possible solutions to address code-mixing. The research employs a descriptive qualitative design with an ethnographic approach, using both primary and secondary data sources. The findings of this study indicate that code-mixing occurs among students at the Islamic boarding school Dārul Lugah Waddirāsātil Islāmiyah, Seninan Akkor, Palengaan, Pamekasan, Madura. Four forms of code-mixing were identified among the students: code-mixing at the word level, phrase level, the use of “baster” forms, and code-mixing involving reduplication. In addition to these forms, eight factors were found to contribute to the occurrence of code-mixing: the speaker’s intention to explain or interpret meaning, the use of more popular terms, the speaker’s personality, the interlocutor, the presence of a third speaker, the topic of conversation, limited mastery of Arabic vocabulary, and insufficient understanding of grammatical rules (qawā’īd). The study also proposes several solutions, including creating an Arabic-speaking environment, enforcing consistent sanctions, teaching vocabulary according to its contextual use, increasing vocabulary memorization, exposing students to Arabic videos, audio materials, or films, providing opportunities for practice, organizing discussion sessions (munāqasyah), strengthening language regulations, assigning dormitory rooms based on language proficiency, implementing disciplinary measures by caregivers, enhancing teacher motivation, encouraging students to record essential vocabulary, and requiring teachers to use Arabic daily